Expression levels of interleukin-17 and interferon-γ in peripheral blood and relationship with thyroid function in patients with Hashimoto’s thyroiditis - Huang, Zhiyong; Zhang, Jiaming; Chen, Si; Mao, Mingfeng; Wang, Boyong (Frontiers in Molecular Biosciences, 2025)
ObjectiveThis study aims to unveil the interleukin-17 (IL-17) and interferon-gamma (IFN-γ) levels in the peripheral blood of patients with Hashimoto’s thyroiditis (HT) and their association with thyroid function.MethodsWe selected 68 HT patients admitted to our hospital and 36 healthy individuals undergoing physical examinations as controls. Clinical data were collected, and serum IL-17 and IFN-γ levels were measured. The Pearson method was used to analyze the correlations between IL-17 and IFN-γ levels and thyroid function parameters. A logistic regression analysis model was employed to evaluate the influencing factors of HT. ROC curves were utilized to assess the diagnostic value of IL-17 and IFN-γ for the occurrence of HT.ResultsSerum IL-17 and IFN-γ levels were higher in both HT patients with hypothyroidism and those without hypothyroidism compared to healthy controls (P < 0.05). IL-17 levels demonstrated a positive correlation with TGAb, TPOAb, and TSH among HT patients, while showing a negative correlation with FT4 (P < 0.05). Similarly, IFN-γ levels were positively related to TGAb and TPOAb (P < 0.05). IL-17 and IFN-γ levels were identified as influencing factors for the occurrence of HT (OR: 1.012, 1.028; P < 0.05). The optimal cutoff values for distinguishing HT from healthy controls were >629.77 pg/mL for IL-17, >286.04 ng/L for IFN-γ, and (>683.02 pg/mL, >252.73 ng/L) for the combination of both. The areas under the curves were 0.854 (0.771–0.936), 0.795 (0.697–0.894), and 0.903 (0.846–0.960), respectively.ConclusionSerum IL-17 and IFN-γ levels are highly expressed in HT patients, and both are closely related to thyroid function and autoantibody levels. They possessed a certain value for the early diagnosis of HT.